A dynamic forward-citation full path model for technology monitoring: An empirical study from shale gas industry. (1st November 2017) - Wei, Yi-Ming; Kang, Jia-Ning; Yu, Bi-Ying; Liao, Hua; Du, Yun-Fei
Highlights: A dynamic model is investigated to monitor the key technical development paths. The status quo of technical innovation of shale gas are quantitatively analyzed. Five potential hotspots are identified using topic modeling. A visualization of technology clusters was carried out by text mining. Simulation, deep fracturing and water treatment are supposed to have good prospect. Abstract: The utilization of shale gas has become one of the important options to transit into low-carbon economy in the world and its vigorous development relies on successful technology revolution to a great extent. Based on patent data, this paper analyzes the development trends and the status quo of technical innovation of shale gas quantitatively by means of patent maps. A new dynamic model named Forward-Citation Full Path (FCFP) is investigated to identify the key development paths in technology clusters and monitor potential breakthrough technologies on those key paths. Then we employ topic modeling and text mining for patent abstracts to explore the potential promising topics with high innovation activeness in aid of providing specific references for development and foresight of the shale gas technology. The results show that: (1) The patent center of shale gas has been transferring from North American to the Asia-Pacific region and the technological innovation is mainly driven by preferential tax policy and loose environmental regimes. (2) Current hotspots of shale gas technology are production technique including stimulation treatments, environmental protection technology of fracturing fluid and geological prospecting technology. (3) There are five potential topics with high innovation activeness identified by topic modeling and text mining which are synthetic carbon oxide, hydraulic fracturing, fracturing propping agents, horizontal well, and technologies of reservoir exploration and modeling. (4) By means of visualization of technology clusters, it is found that promising technologies are refined simulation technology for shale gas exploration, multi-interval fracturing techniques in horizontal wells with deep pay zones, water treatment and environmental protection technology in shale gas production. (5) The suggested dynamic FCFP model can effectively identify the key development paths and monitor potential breakthrough technology of shale gas.